Calculation of the density of states and the thermal properties of polymer chains and stars on a lattice by the Monte Carlo method with the use of the Wang-Landau algorithm - Silantyeva, I.A.; Vorontsov-Velyaminov, P.N. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
The Monte Carlo method with the use of the Wang-Landau algorithm is applied to study the lattice models of free polymer chains and 6-arm polymer stars. The ratio of self-avoiding walks among semi-phantom walks for the chains of length N ≤ 300 and the stars with the total number N ≤ 720 of segments is determined. The distribution over the number of monomers’ contacts for chains and stars with the number N = 30,72,120 of segments is obtained. Based on this distribution, the temperature dependences are found for the internal energy, the heat capacity, and the entropy.